Delimitação espacial e simulação hidrossedimentológica na bacia do rio Japaratuba Mirim em Sergipe - Santos, Thiago Tavares (2010)
The watershed degradation due to human actions such as deforestation, inappropriate land use in agriculture and increased urbanization, associated with extreme natural phenomena, has caused marked structural changes in the agroecosystems. Minimize the negative effects of these changes is a major challenge to be overcome in coming decades. Mostly the watershed occupy large areas and the difficulty in measuring and displaying the data changes over time becomes increasingly difficult. For this purpose software processing and georeferencing of satellite images have been used ensuring outstanding contributions to the study of watersheds. Given the scarcity of relevant data and information about the current situation of water resources, the use of geographic information systems (GIS) is increasingly common and essential in the prediction of hydrologic data and sediment, mainly through modeling or simulation of natural phenomena. Given the importance of watersheds as planning units, aimed to delineate the present work through of the GIS the outline Japaratuba Mirim watershed in Sergipe/Brazil and simulate their runoff and sediment yield.